2016
DOI: 10.1007/s00421-016-3484-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in functional performance with high-speed power training in older adults is optimized in those with the highest training velocity

Abstract: There is considerable variation in self-selected maximal limb velocity during HSPT in older adults. In the present cohort, an average limb velocity of 0.88 m/s during HSPT was necessary to ensure optimal improvement in functional performance for older adults, but this threshold will need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Interestingly, the magnitude of the RFD enhancement seems to be independent of the ballistic-intended movements in elderly persons. It is important to emphasize that the maximal limb velocity during the explosive training can be highly variable in elderly persons (Sayers et al, 2016), which could theoretically attenuate the traininginduced changes in RFD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the magnitude of the RFD enhancement seems to be independent of the ballistic-intended movements in elderly persons. It is important to emphasize that the maximal limb velocity during the explosive training can be highly variable in elderly persons (Sayers et al, 2016), which could theoretically attenuate the traininginduced changes in RFD.…”
Section: Discussionmentioning
confidence: 99%
“…Further, knee angular velocities in the 180 to 300 deg s −1 range are close to those observed during chair rise and walking, and power obtained at these speeds may have greater external validity (Jevsevar, Riley et al 1993). Thus, it is our recommendation that strength and power testing of older adults include high-velocity assessments and exercise interventions incorporate high-velocity exercise training that has been shown to confer functional benefits to both healthy and diseased older adults (Ni, Signorile et al 2016, Sayers, Gibson et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported improvement in physical function following high-speed power training with an average limb velocity of 0.88 m/sec in healthy older adults 19 ) . Others have found that even a progressive heavy-resistance training program of short duration (i.e., 8 weeks) can produce dramatic improvements in muscle strength as well as significant muscular hypertrophy in physically active older women 20 ) .…”
Section: Discussionmentioning
confidence: 99%